Reading in Elected Issues From Grammarians and Quran Book - Ali, Zuhair Mohammed (Al-Adab Journal, 2018)
The book "The grammarians and the Quran" by our Sheikh Dr. Khalil Bounian Al-Hassoun is one of the most important books dealing with the treatment of grammarians with the book of Allah and the miracle of his eternal prophet the Holy Quran, in particular what came out of it is inconsistent with those grammar and grammatical principles that settled in the minds of the grammarians after their interpretation of the words The book follows carefully the position of the grammarians on these issues and what they called the Holy Quran of the epithets are not worthy of his great position. This research aims to follow the issues of the book and re-read a number of texts mentioned by the grammarians, and clarify what they threw, and what they meant, In understanding those texts, or b The other readings that can be carried on it, and what is derived from them. It preserves the grammar and preserves the glorious Quran. Try to re-read the Qur’anic texts that appear to have come from the analogy of the grammarians, or come to the uncommon of their words, The difference between the Arabic texts (poetic or prose) and the Qur’anic text. The search also sought to stand up to those Qur’anic texts and follow the words of the exponents in them to reveal the secret of the rhetorical, the semantic joke, and the expressive affliction for which the Quran This miraculous use